GRADUATE PROGRAM IN EDUCATION OF THE UNIVERSIDADE FEDERAL DA PARAÍBA (PPGE/UFPB): : BETWEEN CELEBRATION AND REMEMBRANCE (1977-1994) - Ivo, Felipe Cavalcanti (2023)
This article intended to disseminate the first analyzes and impressions regarding the constitution and initial trajectory of the Graduate Program in Education of the Universidade Federal da Paraíba (PPGE/UFPB), in favor of Popular Education, between 1977 and 1994. Fulfilling this intention, the following questions were asked: what do historical sources reveal about the Program? What are the first impressions about the identity and social place of the institution, between 1977 and 1994? Why celebrate and remember the initial trajectory of the PPGE/UFPB? From this perspective, bibliographical research and analysis of written memories of historical sources were used as methodology: CONSEPE's Resolution 47º/1977, the Selection Map (profile of candidates) from 1987 to 1994 and the commemorative book marking the 30th anniversary of the Program, dialoguing with Lampert (2000), Saviani (2008), Ferreira (2012), among other authors. As a result, the frame mobilization of the Program in the survey of sources and reflections about the limits of the acts of celebration and remembrance in the celebrative work and in the writing of the first impressions about the History and Memories of the PPGE/UFPB was evidenced.